Annual Clinical Audit of Indoor, Dhaka Dental College and Hospital (January 2004 - December 2005) (Bangladesh Journal of Dental Research & Education, 2015)
Clinical audit of indoor, Dept. of Oral and Maxillofacial Surgery, Dhaka Dental College and Hospital was performed for two years, January 2004 to December 2005. Data included all the indoor patients who were admitted for elective surgery. Day cases were excluded from the study. The audit was performed to assess the nature of pathology and number of patients admitted for surgical treatment. Bangladesh Journal of Dental Research and Education Vol.5(2) 2015: 37-39